Penyuluhan Pentingnya Konsumsi Buah dan Sayur pada Remaja di Sos Desataruna Jakarta - Ni Luh Widani (Patria : Jurnal Pengabdian Kepada Masyarakat, 2019)
Vegetables and fruit are important nutrients that our body needs to fulfill fiber, vitamins, minerals and some enzymes that play an important role in the functioning of the digestive system, cardiovascular system and prevent diabetes mellitus. A survey found that the consumption level of fruits and vegetables in Indonesia was still low. One factor in the low consumption of fruits and vegetables is the development of fast food. Teenager is the group of age with the least consumption of fruits and vegetables. This counseling activity was carried out to find out and increase the knowledge of teenagers about the consumption of fruits and vegetables. This activity was held in SOS Taruna Village which began with the distribution of questionnaires to 35 teenagers who were present at the time of data collection. After the data was obtained, health counseling and distribution of fruits (oranges and bananas) were carried out. The survey results obtained were mostly good at 51.4% and lack of attitudes  (51.4%). Conclusion: teenagers' knowledge and attitudes about consumption of fruits and vegetables is still lacking. Suggestion: need health education and movement to make teenagers aware of the benefits and importance of eating fruits and vegetables and then evaluated in their daily diet.